PREPARATION, EVALUATION AND STABILITY OF LAMIVUDINE LOADED ALGINATE-TAMARIND MUCILAGE MICROSPHERES - Gada, Santosh; Y., ANANDKUMAR; SETTY, C. MALLIKARJUNA (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of the present study was to investigate the possibility of obtaining a controlled, relatively constant effective level of lamivudine microspheres. Methods: Lamivudine loaded sodium alginate (SA) and tamarind mucilage(TM) mucoadhesive microspheres were prepared by ionic gelation technique with three different proportions of SA and TM with different concentrations of CaCl2. The prepared microspheres were evaluated for drug loading, particle size distribution, surface morphology, FTIR, in vitro wash off, in vitro release and stability studies. Results: The microspheres were found to be free flowing having diameter ranging from 769.22 to 978.56 µm, drug encapsulation efficiency (DEE) was found to be 65.28 to 92.33%. Percent drug release after 12 h were ranging from 85±1.51 to 97±1.44. In vitro release profile of all formulations shows slow controlled release up to 12 h. In vitro wash off studies shown fairly good mucoadhesivity with 20% microspheres adhered after 6h. Stability studies showed that no significant change in particle size and maximum DEE in comparison to the formulation stored at room temperature. Results: The lamivudine loaded SA-TM mucoadhesive microspheres can be conveniently prepared which showed better result and it may be used full for controlling the drug release and improve the bioavailability.